Revisiting Muslim women's activism - Sur, Esita, author.
1 online resource
Keywords: "This book traces the evolution of organisational activism among Muslim women in India. It deconstructs the "Muslim woman" as the monolith based on tropes like purdah, polygamy, and tin talaq and compels the reader to revisit the question of Muslim women's individual and collective agency. The book argues that the political field, along with religion, moulds the nature and scope of Muslim women's activism in India. It looks at the objectives of four Muslim women's organisations: the Bazm-e-Niswan, the Awaaz-e-Niswaan, the Bharatiya Muslim Mahila Andolan and the India International Women's Alliance (IIWA) in close interaction with the political landscape of Mumbai. The book explores the emergence of gender-inclusive interpretation of Muslim women's rights by Muslim women activists and challenges the dominant and reductionist stereotypes on Muslim women, community, and absolutist ideas of Islam. It argues that Muslim women are not passive victims of their culture and religion, rather they can develop a critique of their marginality and subjugation from within the community. Revisiting Muslim Women's Activism traces the evolution of a community-centric approach in women's activism and records a fragmented view on women's rights from within the community and religious leadership. It also delineates the distinctiveness of this activism that considers religion and culture as resources for empowerment and as sites of contestations. Moreover, the book documents the narratives of Muslim women's struggle and resistance from their location and lived experiences. It will be of interest to students and researchers of women's studies, gender studies, political science, sociology, anthropology, law, and Islamic studies"--